Web monetisation - Catalina Goanta; Alfa Yohanis; Vikas Jaiman; Visara Urovi (Internet Policy Review, 2022)
Web monetisation is the conversion of user traffic into revenue. Initially referring to websites, in more recent years, the meaning of the term has been expanded to refer to non-website traffic, such as social media applications, which this glossary entry gives more attention to. Within social media, the concept of content monetisation has developed as a way to denote the various approaches content creators have in creating online revenue out of the content they produce. This glossary entry provides an overview of the concepts of web and content monetisation, discusses aspects arising out of their interaction, and addresses three main issues currently associated with the term: the interoperability of social media infrastructures, the interoperability of content and web monetisation, and the moderation of content monetised decentrally.
Keywords: 300; Monetisation; Content; Data governance